1999
DOI: 10.1046/j.1440-1622.1999.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Keloids and Hypertrophic Scars: Results With Intra‐operative and Serial Postoperative Corticosteroid Injection Therapy

Abstract: Because of promising results, further use and evaluation of this method of treatment is recommended for large, recurrent and complicated keloids and hypertrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 30 publications
(50 reference statements)
2
50
0
2
Order By: Relevance
“…Therefore, the follow-up period would be a key factor. It has been reported that 5.5-12.9 months elapsed on average until the recurrence following the treatment [7]. At our institution, there were no notable episodes such as tissue atrophy, telangiectasia for- As shown in our case, there is a possibility that keloid might occur in the axilla.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, the follow-up period would be a key factor. It has been reported that 5.5-12.9 months elapsed on average until the recurrence following the treatment [7]. At our institution, there were no notable episodes such as tissue atrophy, telangiectasia for- As shown in our case, there is a possibility that keloid might occur in the axilla.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, local steroid injections are frequently used as adjuvant therapy to surgery for the purposes of inhibiting the expression of collagen genes in patients with keloid [6]. Chowdri et al reported that the recurrence rate was 8.1% during a followup period of 30 months following a concomitant use of surgery with local steroid injections, thus advocating the efficacy of the combination of the two methods [7]. It can therefore be stated that the combination of surgical excision and local steroid injections is currently the most popular modality.…”
Section: Discussionmentioning
confidence: 99%
“…101 Several noncontrolled studies have shown that the majority of patients experience improvement of the keloid without recurrence after steroid injection. [113][114][115][116] In one controlled study, patients with keloid scars underwent surgical excision and were then randomized to corticosteroid injection (16 mg triamcinolone on postoperative days 0, 7, 21, and 35) or radiation therapy (single dose of 700 or 1,000 cGy). After 30 months of follow-up, no significant difference was found between the treatment arms, and only 22% of patients experienced recurrence.…”
Section: Stem Cells In 2009 Biernaskie Et Al Deter-mentioning
confidence: 99%
“…After treating the patients for a minimum of 8 weeks, the majority of patients achieved a greater than 50% response with a mean (SD) scar volume at the start of 0.73 (0.701) mL reduced to 0.14 (0.302) mL. 3 Chowdri et al 4 reviewed their experience with 58 keloids and hypertrophic scars using intralesional corticosteroid injection. After doing serial injections at weekly intervals for 2 to 5 weeks followed by monthly injections for 4 to 6 months, more than 90% of the patients had no evidence of a recurrence at a mean follow-up of 30.5 months.…”
Section: Nonsurgical Therapy Corticosteroidsmentioning
confidence: 99%